Lack of a Unified Global South Voice in Climate Discourse an Ecofeminist Perspective - Ms. Mahnoor Nosherwan; Ms. Bushra Hasnat; Dr. Muhammad Naveed Ul Hasan Shah (`, 2025)
This research precisely divides the profound and persistent fragmentation of the Global South’s voice in international climate discourse. Particularly challenge the conventional wisdom that attributes this disunity to mere diplomatic failures. It posits a more radical and devastating explanation. This crisis is a logical and inevitable outcome of the deeply entrenched, intersecting systems of patriarchy, colonialism, and global capitalism. In this research rigorous ecofeminist theoretical framework has been followed. This study systematically refutes materialist rationalist views and instead argues that the climate crisis is a catastrophic symptom of the same hierarchical ideologies; that sanction the relentless exploitation of both women and nature. Through a qualitative discourse and historical analysis of negotiation texts, institutional reports, and grassroots movements, the paper reveals how the structural reality of "climate colonialism" and the pervasive, pro growth rhetoric of global governance actively reproduce divisions within the Global South. The research concludes that genuine solidarity and a truly effective political voice cannot be achieved by merely reforming a system designed to thrive on such disunity it demands a radical, transformative, and justice oriented paradigm rooted in the decolonial and intersectional praxis of women led movements on the frontlines of the crisis. Keywords: Ecofeminism, Global South, Climate Justice, Colonialism, Patriarchy, Discourse Analysis